source 2007 Duquesne, page 103, Table 1
parameter b
assume b = -2 a
compute T1 = X1^2
compute T2 = X2^2
compute T3 = X1 Z1
compute T4 = X2 Z2
compute T5 = Z1^2
compute T6 = Z2^2
compute T7 = Y1
compute T8 = Y2
compute T9 = T7 T8
compute T7 = T7+T3
compute T8 = T8+T4
compute T3 = T3 T4
compute T7 = T7 T8
compute T7 = T7-T9
compute T7 = T7-T3
compute T4 = T1 T2
compute T8 = T5 T6
compute T1 = T1+T5
compute T2 = T2+T6
compute T5 = T1 T2
compute T5 = T5-T4
compute T5 = T5-T8
compute T1 = T8-T4
compute T2 = T8+T4
compute T6 = b T3
compute T6 = T9-T6
compute T6 = T6 T2
compute T3 = 2 T3
compute T3 = T5 T3
compute T8 = T6+T3
compute X3 = T7
compute Y3 = T8
compute Z3 = T1